Motor Dyscoordination and Alteration of Functional Correlation Between DGKγ and PKCγ in Senescence-Accelerated Mouse Prone 8 (SAMP8) - Tsumagari, Ryosuke; Maruo, Kenta; Nakao, Takaaki; Ueda, Shuji; Yamanoue, Minoru; Shirai, Yasuhito (Frontiers in Aging Neuroscience, 2021)
Senescence-accelerated mouse prone 8 (SAMP8) is an animal model of age-related central nervous system (CNS) disorders. Although SAMP8 shows deficits in learning, memory, and emotion, its motor coordination has not been clarified. We have recently reported that DGKγ-regulated PKCγ activity is important for cerebellar motor coordination. However, involvement of the functional correlation between the kinases in age-related motor dyscoordination still remains unknown. Therefore, we have investigated the motor coordination in SAMP8 and involvement of the functional correlation between DGKγ and PKCγ in the age-related motor dyscoordination. Although 6 weeks old SAMP8 showed equivalent motor coordination with control mice (SAMR1) in the rotarod test, 24 weeks old SAMP8 exhibited significantly less latency in the rotarod test and more frequent slips in the beam test compared to the age-matched SAMR1. Furthermore, 24 weeks old SAMP8 showed the higher locomotor activity in open field test and Y-maze test. Western blotting revealed that DGKγ expression decreased in the cerebellum of 24 weeks old SAMP8, while PKCγ was upregulated. These results suggest that SAMP8 is a useful model of age-related motor dysfunction and that the DGKγ-regulated PKCγ activity is involved in the age-related motor dyscoordination.